Incorporation of silica nanocontainers and its impact on a waterborne polyurethane coating. Issue 10 (12th April 2019) - Loison, Pierre; Debout, Vincent; Groult, Hugo; Creus, Juan; Touzain, Sébastien
Abstract: In the present work, we describe the development and characterization of a versatile smart coating containing an encapsulated inhibitor. This includes the synthesis and characterization of hollow spherical nanocapsules with diameters ranging from 180 to 200 nm. These particles are able to release their payload when exposed to an alkaline environment, what could be induced by corrosion‐linked processes. A corrosion inhibitor, namely 2‐mercaptobenzothiazole has been encapsulated, after what the capsules were incorporated in a polyurethane (PU) matrix; optimization of the process led to homogeneous coatings with a good dispersion of silica assessed by micro‐fluorescence spectroscopy. Electrochemical impedance spectroscopy highlighted a negative effect of the capsules' addition to the PU network, affecting the coating's barrier properties. However, the release of the inhibitor upon water ingress in the coating and potential short‐term protection was seen. Nevertheless, tests conducted on coatings with artificial defects could not lead to a reduction of the corrosion rate, probably due to the large size of the defects. Abstract : The development and characterization of a versatile smart coating containing an encapsulated inhibitor is described. This includes the synthesis and characterization of hollow spherical nanocapsules with diameters ranging from 180 to 200 nm. Electrochemical Impedance Spectroscopy highlighted a negative effect of the capsules' addition to the polyurethane network, affecting the coating's barrier properties.